Preventing the Reintroduction of Malaria in Mauritius: A Programmatic and Financial Assessment - Tatarsky, Allison (Public Library of Science, 2011)
Sustaining elimination of malaria in areas with high receptivity and vulnerability will require effective strategies to prevent reestablishment of local transmission, yet there is a dearth of evidence about this phase. Mauritius offers a uniquely informative history, with elimination of local transmission in 1969, re-emergence in 1975, and second elimination in 1998. Towards this end, Mauritius's elimination and prevention of reintroduction (POR) programs were analyzed via a comprehensive review of literature and government documents, supplemented by program observation and interviews with policy makers and program personnel. The impact of the country's most costly intervention, a passenger screening program, was assessed quantitatively using simulation modeling. On average, Mauritius spent $4.43 per capita per year (pcpy) during its second elimination campaign from 1982 to 1988. The country currently spends $2.06 pcpy on its POR program that includes robust surveillance, routine vector control, and prompt and effective treatment and response. Thirty-five percent of POR costs are for a passenger screening program. Modeling suggests that the estimated 14% of imported malaria infections identified by this program reduces the annual risk of indigenous transmission by approximately 2%. Of cases missed by the initial passenger screening program, 49% were estimated to be identified by passive or reactive case detection, leaving an estimated 3.1 unidentified imported infections per 100,000 inhabitants per year. The Mauritius experience indicates that ongoing intervention, strong leadership, and substantial predictable funding are critical to consistently prevent the reestablishment of malaria. Sustained vigilance is critical considering Mauritius's enabling conditions. Although the cost of POR is below that of elimination, annual per capita spending remains at levels that are likely infeasible for countries with lower overall health spending. Countries currently embarking on elimination should quantify and plan for potentially similar POR operations and costs.